A hyphenated identity: fostering national unity through education in Malaysia and Singapore - Hashim, Rosnani; Tan, Charlene (citiZED, 2009)
Among plural societies, Malaysia and Singapore are two countries in Southeast Asia that face the challenges of ethnic diversity since their independence from British colonial rule. This paper offers a comparative study on Malaysia and Singapore in their governments’ attempts to foster national unity through education. While both the governments adopt cultural pluralism, they have different approaches in the management of ethnic groups. The Malaysian government chooses to promote ethnic Malay interests through affirmative action policies in education, while the Singapore government professes to treat all the ethnic groups equally and claims that social mobility is determined by meritocracy. This paper focuses on the concept of ‘ethnic-national hyphenated identity’ and discusses the curricular challenges common to Malaysia and Singapore. It argues that efforts are needed to encourage the students to possess a greater sense of ethnic understanding and appreciation, coupled with a greater emphasis on critical inquiry and deliberation of ethnic issues in the curriculum.